A Peroxidase/Dual Oxidase System Modulates Midgut Epithelial Immunity in Anopheles gambiae - Kumar, Sanjeev (2010)
Extracellular matrices in diverse biological systems are crosslinked by dityrosine covalent bonds catalyzed by the peroxidase/oxidase system. We show that the Immunomodulatory Peroxidase (IMPer), an enzyme secreted by the mosquito Anopheles gambiae midgut, and dual oxidase (Duox) form a dityrosine network that decreases gut permeability to immune elicitors and protects the microbiota by preventing activation of epithelial immunity. It also provides a suitable environment for malaria parasites to develop within the midgut lumen without inducing nitric oxide synthase expression. Disruption of this barrier results in strong and effective pathogen-specific immune responses.